The functions of polycomb group proteins in T cells - Ting Li (Cell Insight, 2022)
T cells are involved in many aspects of adaptive immunity, including autoimmunity, anti-tumor activity, and responses to allergenic substances and pathogens. T cells undergo comprehensive epigenome remodeling in response to signals. Polycomb group (PcG) proteins are a well-studied complex of chromatin regulators, conserved in animals, and function in various biological processes. PcG proteins are divided into two distinct complexes: PRC1 (Polycomb repressive complex 1) and PRC2. PcG is correlated with the regulation of T cell development, phenotypic transformation, and function. In contrast, PcG dysregulation is correlated with pathogenesis of immune-mediated diseases and compromised anti-tumor responses. This review discusses recent findings on the involvement of PcG proteins in T cell maturation, differentiation, and activation. In addition, we explore implications in the development of the immune system diseases and cancer immunity, which offers promising targets for various treatment protocols.